POLITIK HUKUM PEMBERIAN GRASI,AMNESTI DAN ABOLISISEBAGAI KONSEKUENSI LOGIS HAK PREROGATIF - Fauzi, Suyogi Imam (Jurnal Hukum & Pembangunan, 2021)
The granting of clemency, amnesty and abolition is a prerogative rights owned by the president based on Article 14 of the 1945 Constitution of the of Indonesia (UUD 1945). The long proses of implementing thegranting of clemency, amnesty and abolition after independence to the post-amendment of the UUD 1945 produce a lesson forIndonesia regarding the law shall be correspond in treating prisoners rights properly in accordance with Human Rights. There is a differences regarding the way of granting clemency which is more dynamically developing beside amnesty and abolition is still at a sustain of stagnation even after the amendment UUD 1945, the provisions regarding amnesty and abolition have not been updated. Based on this process, a pattern which forms a legal policyin granting clemency, amnesty and abolition which can be seen from various aspects ranging from function, purpose, addrest, to legal consequences. This paper will discuss in a structured, systematic and comprehensive manner the legal policyof grantingclemency, amnesty and abolition as a logical consequence of the prerogative rights of the presiden.